2017
DOI: 10.1039/c7ra00148g
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of copper ions on chitosan/cellulose acetate blend hollow fiber membrane for protein adsorption

Abstract: The prepared IMAM (CS/CA-Cu) achieved a high adsorption capacity of 69 mg-BSA per g-membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Various studies have been carried out to improve the mechanical strength of CS membranes. Among them, the following methods have been mostly investigated: (1) preparation of composite membranes by coating CS on some polymeric supports such as polyethersulfone (PES) and cellulose membranes or cellulose filter paper , (2) blending CS with other polymers including cellulose acetate (CA) and poly(vinyl alcohol) (PVA) , and (3) incorporation of nanoparticles into CS membranes . The coating method, however, has encountered some problems including detachment of the coated CS film or incomplete and nonuniform coverage of the support membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have been carried out to improve the mechanical strength of CS membranes. Among them, the following methods have been mostly investigated: (1) preparation of composite membranes by coating CS on some polymeric supports such as polyethersulfone (PES) and cellulose membranes or cellulose filter paper , (2) blending CS with other polymers including cellulose acetate (CA) and poly(vinyl alcohol) (PVA) , and (3) incorporation of nanoparticles into CS membranes . The coating method, however, has encountered some problems including detachment of the coated CS film or incomplete and nonuniform coverage of the support membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Since CS has modifiable functional groups, the stability of its blend enhances with other polymeric materials such as cellulose. To modify CS membrane's mechanical strength, many researchers have worked on the blend of CS and CA . Khalil et al studied CS/cellulose blend and reported that the stability of CS‐based materials can be improved by blending them with other compatible biopolymers in particular cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan treatments offer many advantages for regenerated cellulose fibers, such as biodegradability, non-toxicity, improved absorption ability, etc. [12][13][14][15][16][17]. In our research, plasma and ultrasound were used as treatment techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques are available for applying chitosan to cellulose fibers, such as treatments of cellulose fibers with cross linking agents, where cotton fibers are soaked in chitosan solutions [7,8,[12][13][14]. In recent years, many studies have been made on cellulose fibers that are functionalized with chitosan [4][5][6][7][8][9][10][12][13][14][15][16][17][18][19][20][21]. Chitosan treatments offer many advantages for regenerated cellulose fibers, such as biodegradability, non-toxicity, improved absorption ability, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation